ANALISIS KINERJA KEUANGAN USAHA TAHU â€“ TEMPE â€œWENWINâ€ DI DESA SEA KECAMATAN PINELENG KABUPATEN MINAHASA - Winanda Pangestu; Vicky R.B. Moniaga; Theodora M. Katiandagho; Olfie L.S. Benu (Universitas Sam Ratulangi, 2015)
ABSTRACT Â Winanda Pangestu. Financial Performance Analysis of Tahu â€“ Tempe Business â€œWenwinâ€ at Sea Village Pineleng Subdistrict of Minahasa Regency (under the guidance of Vicky R.B. Moniaga, as a Chairman, and Theodora M. Katiandagho and Benu Olfie L.S. as Members). The objective of this reserch to determine the financial performance of the Tahu â€“ Tempe business